Public Interest: Challenges and Possibilities in Identifying the Content of this Notion in Current Issues in Administrative Law - Oana ŞARAMET (Cambridge Scholars Publishing Ltd, 2020)
By exercising its specific powers, the public administration has to find different answers and solutions to respond to the needs of the communities where it has competence. In any community we can identify a multitude of general interests that would be desirable to be realized by the authorities and institutions from the public administration. Unfortunately, most of the time, it is practically impossible to realize all of these public interests at the same time, most often the financial resources available for public administration are insufficient and, for this reason, it is impossible to satisfy all of these legitimate public interests, even if they were identified through an objective process. Accordingly, it is necessary to prioritize these interests, the realization of some of them will became a priority over the others. The public interest is one of the concepts used in the public administration, but is a concept for which it is difficult to construct a unanimously accepted definition, much of the doctrine appreciating that such a definition could not be formulated either. However, we consider that it is possible to establish some elements that are important to identifiy the substance of this legal concept, as well as some steps and principles to be followed by the public administration in order to indicate these interests and, subsequently, to make an hierarchy of public interests that are needed to be satisfied in that community. Thus, first of all the public administration will be forced to consider those public interests that must be realized because they respond to the needs of the community, not to the interests of the governors. In this study we will use specific research methods, such as comparative, grammatical, logical, systemic and teleological one, but also some less common methods for in the field of law, such as the empirical and experimental method, to analyze theoretical and practical aspects considered relevant to our study.
Keywords: public interest; legitimate interest; characteristics; principles and steps to be use for identifying the public interest